2022
DOI: 10.1021/acsanm.2c01317
|View full text |Cite
|
Sign up to set email alerts
|

Au Nanoparticle-Decorated Magnetic CoFe2O4 Core Nanoparticles Functionalized with N-(4-Aminobutyl)-N-ethylisoluminol for Detection of Copeptin

Abstract: Chemiluminescent (CL) functionalized nanomaterials with good CL property, excellent catalytic performance, and fast magnetic separation ability have great help in CL biological analysis. In this study, the magnetic core cobalt ferrite nanoparticles (CoFe2O4 NPs), possessing good peroxidase (POD)-like activity, were synthesized directly by a one-step solvothermal process. Then, N-(4-aminobutyl)-N-ethylisoluminol-gold NPs (ABEI-Au NPs) were modified on the CoFe2O4 NPs surface via a redox method to obtain CoFe2O4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…A new sensing principle is proposed. The immunosensor exhibited excellent analytical performance with a wide detection range of 3.1 × 10 to 3.1 × 10 8 particles/mL and a low detection limit of 2.1 × 10 3 particles/mL, which were better than the vast majority of the reported CL immunosensors. Moreover, the as-developed CL immunosensor is based on a label-free strategy that does not require complex labeling procedures.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…A new sensing principle is proposed. The immunosensor exhibited excellent analytical performance with a wide detection range of 3.1 × 10 to 3.1 × 10 8 particles/mL and a low detection limit of 2.1 × 10 3 particles/mL, which were better than the vast majority of the reported CL immunosensors. Moreover, the as-developed CL immunosensor is based on a label-free strategy that does not require complex labeling procedures.…”
Section: Discussionmentioning
confidence: 90%
“…2 Yang et al synthesized ABEI and gold nanoparticle (AuNP)-functionalized magneticcore cobalt ferrite nanomaterials and used them to develop a label-free CL immunosensor for copeptin detection. 3 Although these label-free strategies based on CL-functionalized MBs have achieved good performance, there are still same drawbacks that need to be improved. It is known that MBs have a non-negligible quenching effect on CL emission, thereby reducing the CL intensity of functionalized materials and affecting the sensitivity of biosensors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nanozymes are of interest because of their high stability and catalytic activity compared to natural enzymes . Transition metal-based nanozymes (TMNs) have gained prominence owing to their environmental friendliness, low cost, outstanding catalytic properties, and ease of synthesis. , Numerous TMNs exhibiting oxidase or peroxidase activity have been synthesized to improve CL efficiency for highly sensitive detection of analytes. , For example, Yang et al synthesized CoFe 2 O 4 with peroxidase-like activity and achieved sensitive detection of copeptin; Yang et al reported CoOOH nanoflakes that exhibited remarkable oxidase-mimicking activity to enhance the luminol CL . Multimetallic materials may exhibit superior catalytic properties compared to their monometallic counterparts because of the synergistic effects of center metals .…”
Section: Introductionmentioning
confidence: 99%
“…25,26 Numerous TMNs exhibiting oxidase or peroxidase activity have been synthesized to improve CL efficiency for highly sensitive detection of analytes. 27,28 For example, Yang et al synthesized CoFe 2 O 4 with peroxidase-like activity and achieved sensitive detection of copeptin; 29 Yang et al reported CoOOH nanoflakes that exhibited remarkable oxidasemimicking activity to enhance the luminol CL. 30 Multimetallic materials may exhibit superior catalytic properties compared to their monometallic counterparts because of the synergistic effects of center metals.…”
Section: Introductionmentioning
confidence: 99%